Improving Critical Thinking Abilities on HOTs Questions through PJBL Model for Students of Elementary School Teacher Education - Putri Nuraini Sari; Wuri Wuryandani; Rahayu Condro Murti (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
The Students who did not meet the criteria for mastering critical thinking and not carry out Project Based Learning in Mathematics courses became passive, did not generate creativity and did not understand the mathematical concepts applied in the previous material in the learning process. The aim of this research was to identify and analyze the improvement of high-level thinking skills that could be obtained through HOTS (High Order Thingking Skill)  questions using the Project Based Learning method. This research was descriptive research with a qualitative approach and it was conducted in second semester students at Sriwijaya University. Data collection techniques through observation, interviews, test and others were used to solve problem and the documentation was used to collect the process data and research results. The results of this research showed that there was a significant increase in acquisition. Application of the PJBL  (Project Based Learning Model) a to critical thinking skills were in cycles 1 and 2, especially at the knowledge level. Based on the research results, the two studies increased critical thinking skills by 66.66% pre-action and 16.66% post-action, increasing to 85.3% in the method Project Based Learning. Apart from that, there was a significant increase in critical thinking skills with the "Very Good" category increasing from 66.67% to 85.3%. This showed that critical thinking skills had a positive impact on learning outcomes and collaborative spirit in the classroom. Overall, this showed that research applying the Project Based Learning method on HOTS questions was used to improve critical thinking skills to be more effective in strengthening problem solving by second semester students of  elementary school teacher education.